Adolescent sexual and reproductive health literacy in Saudi Arabia: The roles of school type and maternal education - Asma Alshanqiti; Reem F. Al-Mughthawi; Elaf Aljabri; Aisha R. Al-Rashidi; Fatema A. Saleh; Raghdah Alrehaili; Taif N. Alahmadi; Mohamed wagdy (PLoS ONE, 2026)
Background Adolescent sexual and reproductive health (SRH) literacy remains uneven in conservative settings. We assessed SRH knowledge among female secondary-school students in Al-Madinah Al-Monawara and examined socio-demographic correlates and parent–daughter communication. Methods Cross-sectional survey of 389 students (grades 10–12) selected via stratified cluster sampling from government and private schools (20 June–20 July 2024). A validated Arabic questionnaire measured domain-specific SRH knowledge (menstruation, reproductive anatomy, contraception, sexual relationships), sexually transmitted disease (STD) awareness, and parent–daughter communication. Analyses included t -tests/ANOVA, Pearson correlations, and multivariable OLS with HC3-robust SEs. Results Knowledge gaps were concentrated in contraception and sexual relationships; 61 students incorrectly endorsed casual contact as a transmission route for STDs. Private-school students had higher composite SRH scores than government-school peers ( t -test, p < 0.01 ). Maternal education correlated with SRH knowledge ( r = 0.38, p < 0.001 ). Scores varied by age (ANOVA F = 4.67, p = 0.009 ), but age was not an independent predictor in regression. In multivariable models, private-school attendance ( β = 0.212, p = 0.018 ) and higher maternal education ( β = 0.043, p = 0.019 ) independently predicted higher SRH knowledge; paternal education, age, and family size were non-significant. Parent–daughter discussions were infrequent; 72% of students supported school-based SRH education. Conclusions SRH literacy among Saudi adolescent girls is uneven, with prominent misconceptions in contraception and transmission. School type and maternal education are actionable levers. Culturally attuned, standardized curricula—especially in government schools—combined with parent-focused communication supports are warranted to close knowledge gaps and reduce stigma.